Watching Giants : the Secret Lives of Whales. - Kelsey, Elin (University of California Press, 2008)
Personal, anecdotal, and highly engaging, Watching Giants opens a window on a world that seems quite like our own, yet is so different that understanding it pushes the very limits of our senses. Elin Kelsey's colorful first-person account, drawing from her rich, often humorous, everyday experiences as a mother, a woman, and a scientist, takes us to the incredibly productive waters of the Gulf of California and beyond, to oceans around the world. Kelsey brings us along as she talks to leading cetacean researchers and marine ecologists about their intriguing discoveries. We encounter humpback wh.